Evidence for the existence of Dm0-like Lamin in Sf9 cells - Wei Wenqiang; Ji Shaoping; Zhang Yinyan (浙江大学学报. 农业与生命科学版)
The nuclear membrane of mammalian cells was composed of inner nuclear membrane, outer nuclear membrane and perinuclear space. The lamina was localized under the nucleoplasm face of inner nuclear membrane. It has been known that the lamina was distributed in the nucleus of mammalian cells, insect cells and plant cells. Lamina plays important roles in the celluar life cycle, including DNA replication, transcription, chromatin organization as well as nuclear assembly. Moreover, lamina is an obstacle for the egress of some viruses, like herpes simplex virus (HSV). Sf9 cells were mostly used for the infection of Autographa californica multiple nucleopolyhedrovirus (AcMNPV). However, there was no comprehensive study to observe whether Sf9 cells also have the lamina. So, it is difficult to know how AcMNPV pass through the lamina of Sf9 cells and then arrive at the inner nuclear membrane for nuclear egress of capsids.To determine the nucleotide sequence of lamin gene in Sf9 cells, we searched the Spodobase database with the known insect lamin genes. The identity of the nucleotide and amino acid sequences of the homologous lamins was respectively analyzed. To analyze the molecular mass of Lamin of Sf9 cells, the monolayer cells were harvested and the whole-cell protein extracts were separated by SDS-polyacrylamide gel electrophoresis (SDS-PAGE) and the protein size of Lamin was detected using Drosophila Dm0 monoclonal antibody ADL67 by Western blotting. To observe the shape and distribution of lamina of Sf9 cells, the living cells were immunostained with ADL67 by immunofluorescence assay.From the Spodobase database, a Dm0-like lamin EST of Sf9 cells was obtained. The nucleotide and amino acid homology comparison indicated that this sequence showed some identities to the lamins of other species, especially Bombyx mori. Western blotting assay showed that the protein size of Dm0-like Lamin of Sf9 cells was approximately 70 ku. Immunofluorescence staining indicated that the observed lamina of Sf9 cells was localized evenly along with the nuclear membrane.These results indicate that the Dm0-like Lamin may exist in Sf9 cells. How the capsids of budded virus of AcMNPV pass through the lamina will depend on the structure and cellular distribution of lamina. If the distribution of lamina in the inner nuclear membrane is discontinuous, the viral capsids will cross the blind spots to arrive at the inner membrane directly. Also, We cannot exclude the possibility that the lattice of lamina of Sf9 cell is enough wide and the layers of lamina are thin, and the capsids will pass through the lattice without difficulties. On the contrary, if the distribution of lamina is compact and the layers of lamina are thick, the baculovirus may disrupt the lamina for capsids egress. This study may lay the foundation for the exploration of the mechanism of baculovirus capsids transport across the lamina.